Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acs.jpcb.6b06002
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Polyelectrolyte Adsorption to a Dielectric Like-Charged Surface

Abstract: We explore, using recently developed efficient Monte Carlo simulation method, interaction of anionic polyelectrolyte solution with a like-charged membrane. In addition to polyions, solution also contains salt with either monovalent, divalent, or trivalent counterions. In agreement with recent experimental observations, we find that multivalent counterions can lead to strong adsorption of polyions to a like charged surface.On the other hand, addition of 1:1 electrolyte diminishes the adsorption induced by the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 64 publications
3
38
0
Order By: Relevance
“…5, the like charge adsorption at s = 0.3 s * ≈ 3.7 × 10 −3 takes place without the occurrence of the CI. This shows the absence of one-to-one mapping between the membrane CI and the like-charge polyelectrolyte-membrane complexation driven by the "salt-induced" image interaction excess; in agreement with the observation of recent Monte-Carlo (MC) simulations [19], the like-charge polyelectrolyte binding may occur at membrane charge strengths well below the threshold (88) required for the onset of the CI. To summarize, at moderate membrane charges s > s * , the like-charge polyelectrolyte binding can occur exclusively as a result of the salt-induced "image-charge" effect enhanced by the dense cations in the close vicinity of the membrane.…”
Section: Strong Membrane Charges: Like-charge Adsorption By Membrane supporting
confidence: 90%
See 2 more Smart Citations
“…5, the like charge adsorption at s = 0.3 s * ≈ 3.7 × 10 −3 takes place without the occurrence of the CI. This shows the absence of one-to-one mapping between the membrane CI and the like-charge polyelectrolyte-membrane complexation driven by the "salt-induced" image interaction excess; in agreement with the observation of recent Monte-Carlo (MC) simulations [19], the like-charge polyelectrolyte binding may occur at membrane charge strengths well below the threshold (88) required for the onset of the CI. To summarize, at moderate membrane charges s > s * , the like-charge polyelectrolyte binding can occur exclusively as a result of the salt-induced "image-charge" effect enhanced by the dense cations in the close vicinity of the membrane.…”
Section: Strong Membrane Charges: Like-charge Adsorption By Membrane supporting
confidence: 90%
“…Taking also into account the 1l limit of the self-energy ∆Ω (1) pp that will be obtained below from Eq. (24), the 1l-level polyelectrolyte grand potential (19) becomes…”
Section: One-loop Formalism Of Electrostatic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological functions of this anionic molecule are intimately related to its electrostatic coupling with the surrounding macromolecular charges. In this context, the like-charge attraction phenomenon plays a capital role in DNA packing around histones [1], the condensation of polymer solutions [2][3][4][5][6][7][8][9], DNA adsorption on anionic substrates [10][11][12][13], and gene delivery techniques [14]. The characterization of like-charge attraction is thus of paramount importance for understanding and controlling in vivo and in vitro biological processes involving DNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The nontrivial effects of surface polarization due to dielectric mismatch have also been addressed in numerous studies in the literature. [16][17][18][19][20][21][22][23] It is shown that polarization effects become particularly pronounced at high dielectric contrasts, [16][17][18][19][20] in the presence of multivalent ions, 21,22 and at highly curved interfaces. 22,23 Essentially, the electric field generated by the ions inside the confinement space polarizes the interface between the media, leading to nonzero induced charges that attract or repel the ions approaching the interface.…”
mentioning
confidence: 99%